Self-Efficacy with Bullying and Cyberbullying Prevention Efforts in Supporting Implementation SDGs: Literature Review - Fitri, Luthfi Nazillatul; Elfina, Iva; Santoso, Syaputra Dwi; Rosmaharani, Shanti (Jurnal Kesehatan Komunitas Indonesia, 2023)
Bullying is any violent behaviour that is perpetrated repeatedly and intentionally against a person or group of weaker groups. Today, it has become a global problem that is often encountered and faced by many people, not only in the real world but also in the virtual world of cyberbullying. This is the cause of the increase in the number graph of people with mental health disorders, thus creating challenges for everyone to control self-awareness. Therefore, self-efficacy is one of the best treatments for each individual to prevent and recover victims because it can give confidence in their self-esteem and build confidence in each individual. This literature review examines the relationship between self-efficacy and efforts to prevent bullying and cyberbullying in support of implementing SDGs in Indonesia. The study used the literature review design by retrieving articles through an electronic database, namely Google Scholar and eResources. All journals were published around 2013–2023, with keywords used to search for articles: self-efficacy, prevention, bullying, cyberbullying, and SDGs. This method is done by analyzing narratives in journals that are found through several stages, which is to collect 659 articles or research results from international standard journals until 7 articles related to the topic are covered. The results of this study show that there is a link between self-efficacy and bullying prevention efforts and cyberbullying that are proven to improve mental health awareness. The implementation of self-efficacy should be done regularly through a sustainable and ongoing system promoted by collaborating with various parties, leading to improvements in mental health quality to lower the rate of mental health disorders.